Phase transformation of iron niobate powders and ceramics synthesized by oxalate route - Phanichphant S. (2014)
A novel oxalate synthesizing route has been developed for the preparation of iron niobate (FeNbO4, FN) powders. Chlorides of iron and niobium were used as the starting precursors. Diethyl oxalate was employed as a precipitating agent to yield iron niobyl oxalate. Well-crystallized single-phase FeNbO4 powder was formed at temperatures over 700 °C. Phase transformation of the calcined powders were investigated using high temperature X-ray diffraction method at temperatures up to 1100 °C and as a function of the calcination temperature from 1100 to 1300 °C by X-ray diffraction method. Particle morphology and size were investigated by Scanning Electron Microscopy (SEM) technique. Iron niobate powders were pressed into pellets and sintered in air at 1100 °C for 8, 12 and 16 h respectively. SEM technique was employed to examine the microstructure of all iron niobate ceramics. X-ray diffraction patterns of all iron niobate ceramics indicated the formation of mostly monoclinic phase in consistency with the JCPDS file number 16-374.